Wastewater management skills of municipal human resources in Songkhla Lake Basin, Thailand - Somtip, Danteravanich (Rangsit Journal of Arts and Sciences, July-December 2014, 2016)
In recent years, Songkhla Lake has been increasingly polluted by urban and industrial wastewater draining into the lake through various canals. This study aims to investigate the limitations of wastewater management skills of municipal human resources operating in Songkhla Lake Basin and to explore how to build them up. The survey study was conducted by using a questionnaire and focus group meeting with 21 municipalities located in Songkhla Lake Basin. It was found that most of the representatives (93%) from municipalities working on water pollution in the Basin were faced with domestic wastewater problems. It was also found that 77% and 71% of them had limited knowledge and skills of domestic wastewater management systems and wastewater treatment system designs, respectively. The results also illustrated that 86% and 79% of them wished to learn more about the specific competency of wastewater treatment system management and how to access the data source of wastewater control and its design criteria, respectively. This information will help the concerned academic organizations in Songkhla Lake Basin to further strengthen the knowledge, skills and competency of the municipal human resources who work on water pollution, and guide them in the right direction.